Effective teaching practices redefined. - Tang, Yee Voon *; Wong, Shae Lynn * (2013)
The education sector in Malaysia is becoming increasingly competitive and in order for the college to emerge at the top, effective teaching that promotes student learning must be emphasized. However, the extent to which lecturers understand the meaning of effective teaching is debatable. Following the framework of Berliner (1988) and Sandholtz (2011), both studies agree that student learning can only occur if teachers deal with classroom management concerns first before focusing on teaching instruction. The latter study even pointed out that teachers are often engaged in instructive methodologies instead of reviewing classroom management as a means of effective teaching. This has triggered us to examine our college lecturers’ perspectives of this issue: to query and inspect the extent of our college lecturers’ understanding of effective teaching and we hope to clarify and redefine the prerequisites of being an effective lecturer. This study is conducted by means of a survey to investigate the responses and views of Sunway College lecturers towards the strategies and approaches they have undertaken in classrooms and will aim to understand the subjective meaning of their experience. In addition, the effectiveness of the strategies and approaches employed by lecturers in class would be evaluated from the students’ viewpoints, in lieu of seeking parallelism in views. The outcome of this investigation is intended to provide our college lecturers a more accurate direction towards an effective teaching practice. In addition, students’ perspectives in productive learning can be reestablished, which would allow us to reflect and improvise on our current teaching skills and ultimately achieve a more successful breakthrough at both ends.